2013
DOI: 10.1371/journal.pone.0073310
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Anti-CD115 Monoclonal Antibody in Mouse Cancer Models through Dual Inhibition of Tumor-Associated Macrophages and Osteoclasts

Abstract: Tumor progression is promoted by Tumor-Associated Macrophages (TAMs) and metastasis-induced bone destruction by osteoclasts. Both myeloid cell types depend on the CD115-CSF-1 pathway for their differentiation and function. We used 3 different mouse cancer models to study the effects of targeting cancer host myeloid cells with a monoclonal antibody (mAb) capable of blocking CSF-1 binding to murine CD115. In mice bearing sub-cutaneous EL4 tumors, which are CD115-negative, the anti-CD115 mAb depleted F4/80+ CD163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…In the transgenic MMTV-PyMT mouse, studies targeting CSF-1R signaling showed contrasting results. In one study, there was no effect on primary tumor growth or metastasis (45); in another study, it reduced primary tumor growth, with no data reported for metastasis (52). Our data showed for the first time that CSF-1R and CSF-1 blockade actually enhanced metastasis in two different preclinical tumor models, providing evidence that such treatment can lead to different outcomes in different breast tumors.…”
Section: Neutrophils Macrophagesmentioning
confidence: 63%
See 1 more Smart Citation
“…In the transgenic MMTV-PyMT mouse, studies targeting CSF-1R signaling showed contrasting results. In one study, there was no effect on primary tumor growth or metastasis (45); in another study, it reduced primary tumor growth, with no data reported for metastasis (52). Our data showed for the first time that CSF-1R and CSF-1 blockade actually enhanced metastasis in two different preclinical tumor models, providing evidence that such treatment can lead to different outcomes in different breast tumors.…”
Section: Neutrophils Macrophagesmentioning
confidence: 63%
“…TAMs TANs Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of lung ×10 6 Cells/g of lung ×10 6 Cells/g of lung ×10 6 Cells/g of lung the more clinically relevant models using immunocompetent mice, anti-CSF-1R has been reported to reduce primary tumor growth (52), and reduce spontaneous metastasis in an osteosarcoma model (51). In the transgenic MMTV-PyMT mouse, studies targeting CSF-1R signaling showed contrasting results.…”
Section: Neutrophils Macrophagesmentioning
confidence: 99%
“…S4D; refs. [28][29][30]. The kinetics of these myeloid populations, including monocyte subsets and macrophages, mirrored that of NK cells, suggesting they might cooperate in preventing metastasis formation in primary tumor-bearing mice.…”
Section: Ly6cmentioning
confidence: 89%
“…Furthermore, the presence of M2 macrophages is also correlated with other signs of tumor progression, such as elevated regulatory T cell counts, induction of angiogenesis, and increase in lymph node metastasis [168][169][170]. A number of experimental approaches targeting M2 macrophage involvement in cancer have shown initial efficacy in vivo and further validate the importance of their presence in the tumor microenvironment [171][172][173][174].…”
Section: Immune Cell Subtypes Summary Of Functions Referencesmentioning
confidence: 91%